2005
DOI: 10.1002/art.20966
|View full text |Cite
|
Sign up to set email alerts
|

A new haplotype of PDCD1 is associated with rheumatoid arthritis in Hong Kong Chinese

Abstract: Objective. The programmed death 1 (PD-1) molecule is a negative regulator of T cells, and a genetic association between PD-1 and systemic lupus erythematosus and rheumatoid arthritis (RA) in Caucasians has been reported. The aim of this study was to investigate the association of PDCD1 polymorphisms and haplotypes with RA in the Chinese population.Methods. Three single-nucleotide polymorphisms (SNPs), PD-1.1 G/A, PD-1.3 G/A, and PD-1.5 C/T, were genotyped in 180 patients with RA and 647 healthy controls in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
4
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 15 publications
8
103
4
3
Order By: Relevance
“…The cross-reactivity of ASAs with other auto-antibodies, including antithymocyte antibody, antinuclear antibody, antiphospholipid antibody, demonstrated in other studies [19], suggesting a polyclonal B-cell activation, similar to that seen in other autoimmune diseases (e.g. lupus erythematous) might implicate in the development of ASA-related infertility.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The cross-reactivity of ASAs with other auto-antibodies, including antithymocyte antibody, antinuclear antibody, antiphospholipid antibody, demonstrated in other studies [19], suggesting a polyclonal B-cell activation, similar to that seen in other autoimmune diseases (e.g. lupus erythematous) might implicate in the development of ASA-related infertility.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have shown that PD-1 gene polymorphisms are correlated with autoimmune diseases such as ankylosing spondylitis [17], rheumatoid arthritis [10], and systemic lupus erythematous [20]. Moreover PD 1.3 SNP has been reported in different autoimmune settings, including rheumatoid arthritis [14], Type I diabetes [11], Multiple sclerosis [15], Ankylosing spondylitis [16] and Allergy [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While autoimmune diseases have been linked with genetic polymorphisms of co-stimulatory markers [21,22], the functional implications have not yet been fully deciphered. Genetic polymorphism, of course, may compromise not only the function of these molecules but their detection by antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Kong et al demonstrated that SNP PD-1.3 was nonpolymorphic among both patients with RA and controls in Hong Kong Chinese, and that PD-1.1 G/ A in the promoter (position -531 from the translation start) was associated with RA patients in their population. They also investigated whether the haplotype containing PD-1.1G and PD-1.5T was a risk factor for RA (Kong et al 2005).…”
Section: Introductionmentioning
confidence: 99%